Legal Forms Against Corporations as Perpetrators of Environmental Crime in Indonesia: Study Based on the Environmental Protection and Management Law - Natsir, Muhammad; Ulya, Zaki; Rachmad, Andi; Krisna, Liza Agnesta (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2024)
The Indonesian Criminal Code regulates as a legal subject is a natural person. The development of criminal law in Indonesia has made the perpetrators not only individuals but also corporations. Where corporations are legalised by the state through legislation. One of the Indonesian laws that regulates corporations as offenders is Law of the Republic of Indonesia No. 32 of 2009 on Environmental Protection and Management. The companies in environmental management can control community land with the status of Cultivation Rights Title and Building Rights Title. In reality, however, the regulation of companies as perpetrators of crimes is still weak and there is no uniformity of regulation to have a deterrent effect. The method used in this paper is normative jurisprudential legal research, focusing on the identification of criminal sanctions against corporate environmental offenders, with a legal approach. The results of the research showed that the criminal regulation against the perpetrators of criminal acts has been regulated as an ultimum remedium for certain cases, but it is less assertive towards the victims of criminal acts and requires a firm and fair regulation and binds all parties involved in the legalisation of the corporation and the protection of its victims. The legal regulation of corporate criminal offences in the Criminal Code has not been clearly regulated, but in the Law of the Republic of Indonesia No. 32 of 2009 on Environmental Protection and Management, as one of the sectoral laws, the regulation has been carried out, but has not adopted the legal wisdom prevailing in the community, although it has been established.